The Effect Of Incentives On Employee Job Satisfaction At PT Anugerah Firdaus Mandiri : Financial Incentives And Non-Financial Incentives - Achmad Fauzi; Koerniawan Hidajat (UNIVED Press, 2024)
In the era of globalization and intense business competition, companies must improve their performance and productivity by ensuring high employee job satisfaction. This study aims to examine the influence of financial and non-financial incentives on employee job satisfaction at PT Anugerah Firdaus Mandiri. This research uses the questionnaire distribution method with all 45 employees of PT Anugerah Firdaus Mandiri as the sample. Data were collected through Likert scale-based questionnaires and analyzed using multiple linear regression with SPSS 22 software. The study shows that financial and non-financial incentives have a significant impact on employee job satisfaction at PT Anugerah Firdaus Mandiri. The adjusted R-squared coefficient of 0,464 indicates that the regression model explains 46,4% of the variation in employee job satisfaction. These results highlight the importance of incentives in enhancing job satisfaction, suggesting that management should focus on incentive policies to improve employee effectiveness and productivity.